Book Symposium. Steffen Borge, The Philosophy of Football. Issue 3 (3rd July 2022) - Borge, Steffen; Morgan, William J.; Smith, Murray; Weatherson, Brian
ABSTRACT: This is a book symposium on Steffen Borge's The Philosophy of Football . It has contributions from William Morgan, Murray Smith and Brian Weatherson with replies from Borge.